NU Menangkal Gerakan Islam Transnasional: Stategi Penguatan Islam Nusantara Perspektif Kebudayaan Masyarakat Nahdliyin - Parawati, Erina Dwi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The current pattern of transnational Islamic movements can be said to be quite successful in gaining institutional position and discourse on Islamic thought in Indonesia. Nahdlatul Ulama (NU) as a moderate Islamic religious organization is trying to counter this movement pattern through a strategy of strengthening Indonesian Islam. This article aims to understand and explain the strategy for strengthening Nusantara Islam from the cultural perspective of the Terban Village NU community towards the escalation of the transnational Islamic movement. This article's method is qualitative-based with observation, interviews and documentation as data collection techniques which are supported by primary data in the form of books, journals and other articles that are significant to this research. The results of this research show that NU culture, which was used as a strategy to strengthen Indonesian Islam in Terban Village amidst the escalation of the transnational Islamic Movement, played a very vital role. However, the strategy to strengthen Indonesian Islam in Terban Village is not only through preserving NU culture, but also through strengthening the aqidah of ahlussunnah wal jamaah an-nahdliyah which is carried out at various levels of education, autonomous bodies and NU organizations such as Fatayat, Muslimat, Ansor Youth Movement, Ikatan Nahdlatul Ulama Students (IPNU), and the Nahdlatul Ulama Women's Student Association (IPPNU).